Theory Meets Experiment: Metal Ion Effects in HCV Genomic RNA Kissing Complex Formation - Sun, Li-Zhen; Heng, Xiao; Chen, Shi-Jie (Frontiers in Molecular Biosciences, 2017)
The long-range base pairing between the 5BSL3.2 and 3´X domains in hepatitis C virus (HCV) genomic RNA is essential for viral replication. Experimental evidence points to the critical role of metal ions, especially Mg2+ ions, in the formation of the 5BSL3.2:3´X kissing complex. Furthermore, NMR studies suggested an important ion-dependent conformational switch in the kissing process. However, for a long time, mechanistic understanding of the ion effects for the process has been unclear. Recently, computational modeling based on the Vfold RNA folding model and the partial charge-based tightly bound ion (PCTBI) model, in combination with the NMR data, revealed novel physical insights into the role of metal ions in the 5BSL3.2-3´X system. The use of the PCTBI model, which accounts for the ion correlation and fluctuation, gives reliable predictions for the ion-dependent electrostatic free energy landscape and ion-induced population shift of the 5BSL3.2:3´X kissing complex. Furthermore, the predicted ion binding sites offer insights about how ion-RNA interactions shift the conformational equilibrium. The integrated theory-experiment study shows that Mg2+ ions may be essential for HCV viral replication. Moreover, the observed Mg2+-dependent conformational equilibrium may be an adaptive property of the HCV genomic RNA such that the equilibrium is optimized to the intracellular Mg2+ concentration in liver cells for efficient viral replication.